Evaluation of occupational and professional profiles in Ecuadorian context based on guide of Knowledge SWEBOK and ontological model - Quezada Sarmiento, P. (2016)
Bodies of Knowledges (BOKS) contain the relevant knowledge for a discipline and it is necessary for the development of the science and application in the professional and occupational profiles and the possible incidence in the industry of Ecuador. In this paper, it is shown an evaluation of professional and occupational profiles based on standard Software Engineering Body of Knowledge (SWEBOK) 2004 (Spanish Version) and ontological model is showed in order to obtain the necessary information to establish the relationship and the criteria to evaluate the profiles based on the guide of Knowledge.